RNA around the clock - Nolte, Christine; Staiger, Dorothee (Frontiers in Plant Science, 2015)
The circadian timing system in plants synchronizes their physiological functions with the environment. This is brought about by a global control of the gene expression program with a considerable part of the transcriptome undergoing 24-h oscillations in steady-state abundance. These circadian oscillations are driven by a set of core clock proteins that generate their own 24-h rhythm through periodic feedback on their own transcription. Here we provide an update review on molecular events at the RNA level that contribute to the 24-h rhythm of the core clock proteins and shape the circadian transcriptome. We focus on RNA-based regulation in the circadian system of the model plant Arabidopsis thaliana but also discuss selected regulatory principles in other organisms.